Who are the women who relinquish infants for adoption? Domestic adoption and contemporary birth motherhood in the United States. Issue 2 (9th May 2022) - Sisson, Gretchen
Abstract: Introduction: The social context of pregnancy decision‐making has changed in recent decades in the United States (US), but little research has examined how these changes manifest in the context of infant adoption. Methods: To create an updated profile of US birth mothers, this analysis uses demographic data collected and aggregated from six adoption agencies, with information on 8658 private adoptions that occurred between 2011 and 2020. Results: Based on this sample, birth mothers today are older and more racially and ethnically diverse than counterparts in previous generations; a majority have other had children and a substantial proportion were parenting other children at the time of relinquishment. They report living on low incomes and, when considered with other measures (e.g., employment, health insurance, homelessness), seem to lack the economic resources that would give them meaningful power over the options available to themselves and their children. Most birth mothers contact agencies late in their pregnancies or after delivery, at a point when abortion care is likely inaccessible or unavailable. An important minority of birth mothers will relinquish more than one infant for adoption over the course of their reproductive lives. Conclusion: Given the underlying shift in the demographic profile of women who relinquish infants, it is likely that the underlying circumstances that lead to adoption have also diverged. More research is needed into how women make decisions about adoption; such research carries implications for how best to support women's decision‐making and ensure access to needed services throughout pregnancy and beyond.